SCR7, an inhibitor of NHEJ can sensitize tumor cells to ionization radiation. Issue 9 (30th June 2021) - Gopalakrishnan, Vidya; Sharma, Shivangi; Ray, Ujjayinee; Manjunath, Meghana; Lakshmanan, Divya; Vartak, Supriya V.; Gopinatha, Vindya K.; Srivastava, Mrinal; Kempegowda, Mantelingu; Choudhary, Bibha; Raghavan, Sathees C.
Abstract: Nonhomologous end joining (NHEJ), one of the major DNA double‐strand break repair pathways, plays a significant role in cancer cell proliferation and resistance to radio and chemotherapeutic agents. Previously, we had described a small molecule inhibitor, SCR7, which inhibited NHEJ in a DNA Ligase IV dependent manner. Here, we report that SCR7 potentiates the effect of γ‐radiation (IR) that induces DNA breaks as intermediates to eradicate cancer cells. Dose fractionation studies revealed that coadministration of SCR7 and IR (0.5 Gy) in mice Dalton's lymphoma (DLA) model led to a significant reduction in mice tumor cell proliferation, which was equivalent to that observed for 2 Gy dose when both solid and liquid tumor models were used. Besides, co‐treatment with SCR7 and 1 Gy of IR further improved the efficacy. Notably, there was no significant change in blood parameters, kidney and liver functions upon combinatorial treatment of SCR7 and IR. Further, the co‐treatment of SCR7 and IR resulted in a significant increase in unrepaired DSBs within cancer cells compared to either of the agent alone. Anatomy, histology, and other studies in tumor models confirmed the cumulative effects of both agents in activating apoptotic pathways to induce cytotoxicity by modulating DNA damage response and repair pathways. Thus, we report that SCR7 has the potential to reduce the side effects of radiotherapy by lowering its effective dose ex vivo and in mice tumor models, with implications in cancer therapy.